Postharvest Adaptation Strategies to the Effects of Temperature Variations and Farmer-Miller Practices on the Physical Quality of Rice in Cameroon - Ndindeng, S.A.; Mapiemfu, D.L.; Fantong, W.; Nchinda, V.P.; Ambang, Z.; Manful, J.T. (Scientific Research Publishing, Inc., 2014)
In order to develop simple and adaptable measures to reduce the impact of changing climatic conditions and poor postharvest practices on grain quality, data on temperature and postharvest practices were collected and correlated with physical grain quality parameters for 3 rice development hubs (Ndop, Lagdo and Mbam) in Cameroon. Inter-annual variations in temperature and thermal amplitudes were the highest in Ndop followed by Mbam and the least in Lagdo. When the same rice variety was grown in the hubs and milled with a laboratory hand dehusker, the mean chalky score was highest in Ndop (18%) and least in Mbam (11%). In addition, Ndop recorded higher grain fissures and broken fractions compared to Mbam or Lagdo. Positive correlations were observed between thermal amplitudes, grain fissures and the proportion of broken fractions. However, rice milled using commercial mills located in the hubs recorded the highest broken fractions in Mbam (54% - 63%), followed by Lagdo (43% - 52%) and the least in Ndop (35% - 38%). The type of mills in the hubs was responsible for these differences as Mbam had only Engelberg types mills that recorded higher broken fractions than in Ndop where only rubber roll mills were present (P < 0.05). Lagdo had a mixture of Engelberg and rubber roll mills and recorded intermediate broken fractions. Proper parboiling, recovery and processing of poorly filled and immature grains during parboiling and processing of low-grade and fine broken rice into product generally accepted by the local population were demonstrated as simple adaptation strategies to mitigate the adverse effects of changing climatic conditions and poor postharvest practices on the physical quality of rice especially in sub-Saharan African countries.